COMPARISON OF PARAMEDIAN WITH MIDLINE TECHNIQUE OF SPINAL ANAESTHESIA IN ELDERLY: Spinal Anaesthesia - Shehzad, Farrukh; Haider, SM Zaheer; Zafar, Bushra; Malik, Hamza; Jahangir, Muhammad Adil; Kirwan, Saqib (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the technique of paramedian with midline approach of subarachnoid block in terms of number of attempts and frequency of success rate in elderly patients undergoing elective lower body surgeries. Study Design: Randomized controlled trial. Place and Duration of Study: This study was carried out at Anaesthesia department of Combined Military Hospital Lahore. Six months from Jan 2014 to Jun 2014. Material and Methods: One hundred and seventy elderly patients were scheduled for lower body surgery, using spinal anaesthesia. They were randomized to either Midline approach (n=85) or Paramedian approach (n=85) by lottery method. The outcome measures number of attempts and success rate were noted in both groups and analyzed using SPSS version 18. Results: The successful block in first attempt was 95.3% in Paramedian group and 58.8% in Midline group. Mean number of attempts in paramedian group was 1.24 ± 0.52 as compared to 1.95 ± 0.97 in midline group. A p-value <0.05 was taken significant. Conclusion: The Paramedian technique was found associated with higher success rate, lesser possibility of repeated number of attempts in elderly patients as compared to Midline approach.